2000
DOI: 10.1126/science.289.5478.457
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Basis for General Intelligence

Abstract: Universal positive correlations between different cognitive tests motivate the concept of “general intelligence” or Spearman's g . Here the neural basis for g is investigated by means of positron emission tomography. Spatial, verbal, and perceptuo-motor tasks with high- g involvement are compared with matched low- g control tasks. In contrast to the common view that g reflects a broad sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
477
2
16

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 937 publications
(531 citation statements)
references
References 16 publications
36
477
2
16
Order By: Relevance
“…The neural underpinnings of generalized intelligence, which has long been considered primarily, if not exclusively, a psychometric abstraction, have only recently begun to be elucidated. These data, with healthy subjects (Duncan et al, 2000;Gray, Chabris, & Braver, 2003) as well as from animal studies (Matzel et al, 2003), generally comport with the current CB correlates, with all pointing to the importance of lateral and medial prefrontal involvement in generalized intelligence. For patients with schizophrenia, functional neuroimaging studies have linked reduced activity of the anterior cingulate cortex to monitoring failures elicited by Stroop conflict stimuli (Carter et al, 2001).…”
supporting
confidence: 68%
“…The neural underpinnings of generalized intelligence, which has long been considered primarily, if not exclusively, a psychometric abstraction, have only recently begun to be elucidated. These data, with healthy subjects (Duncan et al, 2000;Gray, Chabris, & Braver, 2003) as well as from animal studies (Matzel et al, 2003), generally comport with the current CB correlates, with all pointing to the importance of lateral and medial prefrontal involvement in generalized intelligence. For patients with schizophrenia, functional neuroimaging studies have linked reduced activity of the anterior cingulate cortex to monitoring failures elicited by Stroop conflict stimuli (Carter et al, 2001).…”
supporting
confidence: 68%
“…In the Talairach brain, the center coordinate (0, 0, 0) is the intersection of the VCA with the anterior/posterior commissural plane. Because the MNI brain differs in shape and size from the Talairach brain -specifically, "MNI brains are higher, deeper, and longer with increasing differences further from the center of the brain" (Brett et al, 2002) -any MNI coordinates not reported in Talairach space were converted using the transformation equations for above the AC line (z ≥ 0): x′ = 0.9900x, y′ = 0.9688y + 0.0460z, z′ = -0.0485y + 0.9189z (Duncan et al, 2000; http://www.mrccbu.cam.ac.uk/Imaging/Common/mnispace.shtml). For the SMC and LPMC regions, coordinates were stripped of laterality distinction.…”
Section: Inclusion Criteria For Articles and Coordinatesmentioning
confidence: 99%
“…These studies all contrasted free choices with cued choices (In these studies, like in our current study, participants had to make a left or right response either freely or to external cues), as we did in our current study. Two of these studies reported coordinates in Talairach space, we converted these coordinates to MNI coordinates in MatLab using the tal2mni function (http://imaging.mrc-cbu.cam.ac.uk/imaging/MniTalairach; Duncan et al, 2000;Calder, Lawrence, & Young, 2001). Besides the RCZ we also looked at other brain regions that showed significant activation in whole brain analysis, and that are known to be part of the choice network.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%